Progress towards laser plasma based free electron laser on COXINEL. (July 2020) - Couprie, Marie-Emmanuelle; André, Thomas; Blache, Frédéric; Bouvet, François; Dietrich, Yannick; Duval, Jean-Pierre; El-Ajjouri, Moussa; Ghaith, Amin; Herbeaux, Christian; Hubert, Nicolas; Kitégi, Charles; Khojoyan, Martin; et al.
Abstract: The Free Electron Laser (FEL) application of Laser Plasma Acceleration (LPA) requires the handling of the energy spread and divergence. The COXINEL manipulation line, designed and built at SOLEIL for this purpose, consists of high gradient quadrupoles for divergence handling and a decompression chicane for energy sorting, enabling FEL amplification with baseline parameters. Installed at Laboratoire d'Optique Appliquee (LOA), it uses robust electrons generated and accelerated by ionization injection using a 30 TW laser. We report here on the work progress towards a FEL demonstration. The LPA measured electron beam characteristics deviates from the baseline reference case. After the installation of the equipment, the electron beam transport has first been optimized. The electron position and dispersion are independently adjusted. Then, undulator radiation has been measured. The spectral purity is controlled via the energy spread adjusted in the slit located in the chicane. FEL effect demonstration is within reach, with currently achieved performance on different LPA experiments.